1970
DOI: 10.1021/ja00705a014
|View full text |Cite
|
Sign up to set email alerts
|

Electronic energy levels in hexahalotellurate(IV) complexes

Abstract: This change is very rapid for the blue isomer, but relatively slow for the purple isomer.) The weight gained in the formation of the yellow complex, which is identical with the weight loss when the yellow complex is dehydrated to re-form the original blue or purple complexes, corresponds to three molecules of water per Ni(II) ion (Caled: 14.11. Found: 13.9). This yellow complex can be tentatively formulated as ( ) 4( 20)2• 2 . It is significant that in the vibrational spectrum of this complex, the water absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

1971
1971
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 1 publication
0
17
0
2
Order By: Relevance
“…However, some previous observations indicated that the influence of the-ligands is not negligible. If chloride ligands are replaced by broihide tlhe longest-wavelength absorptions of s 2 complexes are apparently shifted to lower energies [11][12][13][14][15][16]. A systematic study of the absorption as well as the emission spectra of the bromo complexes of Sn 2+ , Pb 2+ , Sb 3+ and Bi 3+ was expected to clarify the role of the ligands.…”
Section: Introductionmentioning
confidence: 99%
“…However, some previous observations indicated that the influence of the-ligands is not negligible. If chloride ligands are replaced by broihide tlhe longest-wavelength absorptions of s 2 complexes are apparently shifted to lower energies [11][12][13][14][15][16]. A systematic study of the absorption as well as the emission spectra of the bromo complexes of Sn 2+ , Pb 2+ , Sb 3+ and Bi 3+ was expected to clarify the role of the ligands.…”
Section: Introductionmentioning
confidence: 99%
“…ing the experiments of Couch et al (20), the general conclusion arrived at is that the tellurium employs essentially pure p-orbitals in bonding, the 5s2 electrons being stereochemically nonactive. Thus the T e g -ions are octahedral (21), have relatively long weak Te-X bonds and the 12'Te Mossbauer isomer shifts show a simple trend of increasing positive values (increasing (Y,(0)I2 assuming ARIR is positive) with increasing electronegativity of the ligand.…”
Section: The 12' Te Isomer Shiftsmentioning
confidence: 96%
“…So zeigte das TeB r62~-Ion in K2TeBr6 ü berra schend eine regulär oktaedrische Struktur [4]. Diese wurde durch Ram an-Spektroskopie [5], NQR-Spektroskopie [6 ] und E lektronenspektren [7] bestätigt.…”
Section: Einführungunclassified